The Coffin-Siris syndrome. - Qazi, Q H (1990)
We report a white female infant with typical features of Coffin-Siris syndrome including thick eyebrows, flat nasal bridge, anteverted, wide nose tip, generalised hypertrichosis, scalp hypotrichosis, absence of the fifth fingernails and toenails, absence of the distal phalanges of the fifth fingers and of the second to fifth toes, small patellae, inguinal hernia, and sucking and feeding difficulties. There was decreased fetal activity and intrauterine growth retardation.